PENGARUH LATIHAN SHUTTLE RUN WITH SPEED DRIBBLING TERHADAP MENGGIRING BOLA CLUB SEPAKBOLA GARUDA FC - Didi Pranatha; Slamet Slamet; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The problem in this research is the dribbling of Garuda FC Football Club athlete is still less, the ball is away from the foot so the ball is easily captured by the opponent. This can be seen from various friendly and official matches. The research was conducted at Garuda FC Football Club. The population in this study is Garuda FC Football Club which amounted to 16 people. Exercise in this research is Shuttle Run With Speed Dribbling. This type of research is an experiment to see the effect of the form of exercise. The sampling technique uses total sampling, where the total population is sampled. The data retrieval technique is obtained from pree-test and post test. The research instrument uses the Dribbling Test. The analysis was performed using the t-test. Based on data analysis and discussion, proven with Tcount equal to 3,67 and Ttabel 1,764. Means Tcount> Ttables. At ɑ = 0,05 level. So it can be concluded that there is significant influence from the exercise Run Shuttle with Speed Dribbling Club Football Garuda FC.Keywords: Shuttle Run With Speed Dribbling, Dribble, Football